Pharmacokinetics of phenazone (antipyrine) in rabbits with experimental common bile duct obstruction. - Wójcicki, J. (1996)
1. An altered functional state of liver due to experimental cholestasis could result in a change in the biotransformation of drugs. The aim of this study was to evaluate an influence of obstructive cholestasis on the pharmacokinetics of phenazone (antipyrine). 2. The investigation was carried out on male rabbits, randomly allocated into two groups: shamoperated and animals with biliary ducts ligation. Phenazone was administered intragastrically as a probe of drug metabolism. 3. Measurements, i.e. laboratory and pharmacodynamic tests, as well as pharmacokinetic assays, were performed before the operation as well as 10-12 days after the bile duct ligation. At the end of the study livers were examined macro- and microscopically and biochemical analysis of the liver microsomes was performed. 4. The measured pharmacokinetic parameters suggested an impaired biotransformation of phenazone in animals with obstructive cholestasis, leading to a slower drug elimination.